Microfinance client protection in Asia and the Pacific lessons from ADB-smart campaign training programs. - Shinozaki, Shigehiro (ADB briefs., 2017)
Slower economic growth globally and regulatory tightening in finance has complicated access to finance for vulnerable groups, including low-income households and small businesses. Limited financial access for these groups requires diversified financing modalities accessible to them, addressing the balanced development of banking and nonbank finance industries.